2014
DOI: 10.1088/1748-9326/9/4/044001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of increasing drought severity caused by temperature rise in southern Europe

Abstract: We use high quality climate data from ground meteorological stations in the Iberian Peninsula (IP) and robust drought indices to confirm that drought severity has increased in the past five decades, as a consequence of greater atmospheric evaporative demand resulting from temperature rise. Increased drought severity is independent of the model used to quantify the reference evapotranspiration. We have also focused on drought impacts to drought-sensitive systems, such as river discharge, by analyzing streamflow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
338
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 598 publications
(407 citation statements)
references
References 31 publications
28
338
0
5
Order By: Relevance
“…In the last decades, the severity of droughts in the IP has increased, together with an increased tendency for dryness and decrease of vegetation cover, due to the higher atmospheric evaporative demand [28,37]. These agree with the findings of Greve et al [38] that identified the Southwest of the IP as one hot spot of the pattern "dry gets drier."…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the last decades, the severity of droughts in the IP has increased, together with an increased tendency for dryness and decrease of vegetation cover, due to the higher atmospheric evaporative demand [28,37]. These agree with the findings of Greve et al [38] that identified the Southwest of the IP as one hot spot of the pattern "dry gets drier."…”
Section: Introductionsupporting
confidence: 84%
“…Different sources of data have been used to compute drought indicators including observations from meteorological stations [26][27][28], gridded datasets [22,29], and reanalysis datasets [30]. Several authors have provided evidences of an increasing number of droughts forced by higher temperatures and enhanced dry conditions [28,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…A high number of meteorological drought indices with different intricacy have been utilised in various climatic conditions . Latest drought trend studies (Sheffield et al 2012;Vicente-Serrano et al 2014) and drought scenarios under possible climate change predictions (e.g., Cook et al 2014) depend on indices that take into consideration evapotranspiration and precipitation such as the reconnaissance drought index (RDI), which is considered in this study.…”
Section: Identification Of Droughtmentioning
confidence: 99%
“…In dry areas, water use by irrigation scheduling can be a compromise for environmental sustainability of the crop and sometimes be a competition with other critical human uses ). Moreover, evaporative demand is expected to increase as a consequence of increased global air temperature (Vicente-Serrano et al 2014) and intensity of climatic anomalies, such as droughts and heat waves (IPCC 2013;Jones and Vaughan 2010). These effects could only be alleviated with higher transpiration rates to lower leaf temperature.…”
Section: General Introductionmentioning
confidence: 99%